Overtraining syndrome as a risk factor for bone stress injuries among Paralympic athletes - Madzar, T.; Masina, T.; Zaja, R.; Kastelan, S.; Cvetkovic, J. P.; Brborovic, H.; Dvorski, M.; Kirin, B.; Barisic, A. V.; Cehok, I.; Milosevic, M. (Medicina, 2024)
Background and Objectives: In this review, we have explored the relationship between overtraining syndrome (OTS) and bone stress injuries among paralympic athletes. OTS is a complex condition that arises from an imbalance between training volume, nutrition, and recovery time, leading to significant negative effects on paralympic athlete`s performance and overall well-being. On the other hand, bone stress injuries occur when abnormal and repetitive loading is applied to normal bone, resulting in microdamage accumulation and potential. The prevalence of overtraining syndrome and bone stress injuries among athletes highlights the need for a better understanding of their relationship and implications for prevention and management strategies. Methods: A literature review from the PubMed, Web of Science, and Google Scholar databases including the MeSH keywords "overtraining syndrome", "bone", and "paralympic athletes". Results: Studies have consistently shown that athletes engaged in endurance sports are particularly susceptible to overtraining syndrome. The multifactorial nature of this condition involves not only physical factors, but also psychological and environmental determinants. In addition, the diagnosis and management of OTS and bone stress injuries present challenges in clinical practice. Conclusions: Currently, there are no definitive biochemical markers for overtraining syndrome. The diagnosis is based on a combination of subjective measures such as questionnaires, symptoms checklists, and objective biomarkers, including hormone levels, inflammatory markers, and imaging studies. However, these diagnostic approaches have limitations regarding their specificity and sensitivity.